GlycA for long-term outcome in T2DM secondary prevention. (January 2021) - Zierfuss, Bernhard; Höbaus, Clemens; Herz, Carsten T.; Pesau, Gerfried; Mrak, Daniel; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Abstract: Aims: Glycosylated acetyls (GlycA), a systemic marker of inflammation, were associated both with incident type 2 diabetes mellitus (T2DM) and incident cardiovascular (CV) disease. This study evaluates the predictive value of GlycA for long-term survival in patients with T2DM and peripheral artery disease (PAD). Methods: GlycA (mmol/l) levels were measured by nuclear magnetic resonance spectroscopy in a cross-sectional cohort of patients with PAD (n = 319). Both all-cause and CV mortality were evaluated after a follow-up of 9.0 (IQR 6.5–9.5) years. During the follow-up 117 patients died, of those 64 events were of CV origin (PAD-T2DM subgroup: all-cause mortality n = 60, CV-mortality n = 32). Results: PAD-T2DM showed a tendency towards a worse CV risk factor profile and a higher percentage of known coronary artery disease (24.9% vs 43.5%, p < 0.001). GlycA levels were higher in PAD-T2DM (1.6 ± 0.2 vs. 1.53 ± 0.18, p = 0.002). GlycA predicted all-cause mortality after multivariable adjustment for traditional CV risk factors (HR for 1 SD increase 1.51, 95% confidence interval 1.03–2.19) in PAD-T2DM, while no association could be seen with CV-mortality (1.22, 0.73–2.06). Conclusions: GlycA was capable of predicting long-term outcome in PAD patients with T2DM. Thus, GlycA might reflect the added inflammatory burden of T2DM in systemic atherosclerosis.